Changes in urethral mobility and configuration after prolapse repair. (2nd January 2019) - Wen, L.; Shek, K. L.; Dietz, H. P.
ABSTRACT: Objective: To evaluate changes in urethral mobility and configuration after prolapse repair. Methods: This was a retrospective study of 92 patients who were examined between 2005 and 2016 before and after surgery for pelvic organ prolapse (POP) without concomitant anti‐incontinence surgery. All patients were assessed with an interview, POP quantification and translabial four‐dimensional ultrasound. Urethral mobility was evaluated using semi‐automated urethral motion profile software in which x ‐ and y ‐coordinates of six equidistant points along the length of the urethra were determined both at rest and on Valsalva, relative to the posteroinferior margin of the pubic symphysis. Urethral kinking was measured by placing tangents distal and proximal to any visually identified change in the urethral axis. Imaging data obtained before and after prolapse surgery were compared. Results: Mean age was 58 years and mean follow‐up was 5.8 months. Prolapse symptoms had resolved in 85% of patients. Highly significant reductions in urethral mobility and urethral kinking were seen after surgery (all P  ≤ 0.001). Similar changes were observed after anterior vaginal repair with or without apical repair, without concomitant posterior repair ( n  = 23; all P  < 0.05). Conclusions: POP surgery was associated significantly with 'straightening' of the urethra and reduction in urethral mobility. The effect seems to be due largely to cystocele repair. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.